Wall Shear Stress in the Feeding Native Conduit Arteries of Superficial Arteriovenous Malformations of the Lower Face is a Reliable Marker of Disease Progression - El sanharawi, Imane; Barral, Matthias; Lenck, Stéphanie; Dillinger, Jean Guillaume; Salvan, Didier; Mangin, Gabrielle; Cogo, Adrien; Bailliart, Olivier; Levy, Bernard I.; Kubis, Nathalie; Bisdorff-Bresson, Annouk; Bonnin, Philippe (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To assess the prognostic value of the wall shear stress (WSS) measured in the feeding native arteries upstream from facial superficial arteriovenous malformations (sAVMs). Reliable prognostic criteria are needed to distinguish progressive from stable sAVMs and thus support the indication for an aggressive or a conservative management to avoid severe facial disfigurement.Materials and Methods We prospectively included 25 patients with untreated facial sAVMs, 15 patients with surgically resected sAVMs and 15 controls. All had undergone Doppler ultrasound examination (DUS) with measurements of inner diameters, blood flow velocities, computation of blood flow and WSS of the feeding arteries. Based on the absence or presence of progression in clinical and imaging examinations 6 months after, we discriminated untreated patients as stable or progressive.Results WSS in the ipsilateral external carotid artery was higher in progressive compared to stable sAVMs (15.8 ± 3.3dynes/cm² vs. 9.6 ± 2.0dynes/cm², mean±SD, p < 0.0001) with a cut-off of 11.5dynes/cm² (sensitivity: 92 %, specificity: 92 %, AUC: 0.955, [95 %CI: 0.789–0.998], p = 0.0001). WSS in the ipsilateral facial artery was also higher in progressive compared to stable sAVMs (50.7 ± 14.5dynes/cm² vs. 25.2 ± 7.1dynes/cm², p < 0.0001) with a cut-off of 34.0dynes/cm² (sensitivity: 100 %, specificity: 92 %, AUC: 0.974, [95 %CI: 0.819–1.000], p = 0.0001). The hemodynamic data of operated patients were not different from those of the control group.Conclusion WSS measured in the feeding arteries of an sAVM may be a simple reliable criterion to distinguish stable from progressive sAVMs. This value should be considered to guide the therapeutic strategy as well as the long-term follow-up of patients with facial sAVMs.
Keywords: arteriovenous malformation; blood flow volume; external carotid artery; facial artery; wall shear stress